First Pediatric Outpatient Parenteral Antibiotic Therapy Clinic in Indonesia - Hendarto, Aryono; Putri, Nina Dwi; Yunita, Dita Rizkya; Efendi, Mariam; Prayitno, Ari; Karyanti, Mulya Rahma; Satari, Hindra Irawan; Hadinegoro, Sri Rezeki S.; Chan, Monica (Frontiers in Pediatrics, 2020)
Background: Infection remains a major pediatric health problem in Indonesia and usually leads to longer hospitalization due to the need for extended intravenous antibiotic administration. In developed countries, pediatric outpatient parenteral antibiotic therapy (P-OPAT) is well established and proven to be safe and effective at reducing the length of hospital stay; however, data on low- and middle-income countries such as Indonesia remain limited. This P-OPAT service is new and the first service in Indonesia. Methods: The medical records of patients attending Indonesia’s first P-OPAT clinic between April 2015 and March 2017 were retrospectively investigated. Results: During the 24-month period, 32 patients received treatment at the P-OPAT clinic, saving a total of 258 bed days. The majority of patients (n=16; 50%) were diagnosed with urinary tract infection, followed by cellulitis (n=4; 12.5%) and osteomyelitis (n=4; 12.5%). Ceftriaxone was the most commonly used antibiotic (n=16; 50%). All patients used a peripheral intravenous catheter and were sent home with this device. Twelve patients (37.5%) needed to change IV access more than once. None of the patients used elastomeric infusor device. The median duration of OPAT was 5 days (range 1-27 days). All patients were successfully treated with no recurrence after 30 days. One patient (3.1%) experienced drug-related complication and another one (3.1%) was readmitted due to an underlying medical condition. All the patients complied with P-OPAT schedules. Conclusions: P-OPAT service offers a safe and effective option for the delivery of outpatient intravenous antibiotics in selected patients even in resource-poor settings.